2016
DOI: 10.1177/0272989x16632197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Literacy on Decision-Making Preferences among Medically Underserved Patients

Abstract: Introduction Participation in the decision-making process and health literacy may both affect health outcomes; data on how these factors are related among diverse groups are limited. This study examined the relationship between health literacy and decision-making preferences in a medically underserved population. Methods We analyzed a sample of 576 primary care patients. Multivariable logistic regression was used to examine the independent association of health literacy (measured by the Rapid Estimate of Adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 38 publications
2
60
0
1
Order By: Relevance
“…Given that most of these participants viewed themselves as having poor health literacy, they preferred not to be involved. This finding is consistent with the findings of previous research which shows that poor health literacy is a significant barrier to shared decision-making [55,56]. Therefore, it is proposed that Arabic-speaking immigrants' understanding regarding involvement could be rectified through workshops which could be conducted at Arabic community centres, mosques, and churches.…”
Section: Participation In Decision-makingsupporting
confidence: 91%
“…Given that most of these participants viewed themselves as having poor health literacy, they preferred not to be involved. This finding is consistent with the findings of previous research which shows that poor health literacy is a significant barrier to shared decision-making [55,56]. Therefore, it is proposed that Arabic-speaking immigrants' understanding regarding involvement could be rectified through workshops which could be conducted at Arabic community centres, mosques, and churches.…”
Section: Participation In Decision-makingsupporting
confidence: 91%
“…Health literacy, which is defined as the ability to read, understand, evaluate and use health information to make reasoned, health‐related decisions (Sorensen et al, ), has been reported to be negatively associated with healthcare decision‐making (Seo, Goodman, Politi, Blanchard, & Kaphingst, ; Van der Heide, Uiters, Jantine Schuit, Rademakers, & Fransen, ) and health outcomes including health disparity and mortality (Cutilli, Simko, Colbert, & Bennett, ; Smith, Jackson, Kobayashi, & Steptoe, ). However, another nationwide study reported that although there is a strong relationship between disease‐specific health literacy and knowledge, an association between health literacy and self‐management is not evident (Yeh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy includes self-confidence, social skills, and social networks as well as literacy and numeracy [32-35], and all these dimensions are likely to affect patients’ intention to use a DA [30]. Studies have also demonstrated that health literacy influences patients’ motivation to manage their health [36,37] and their attitude toward SDM, especially their desire for involvement in the decision [31,38-44] and for information [45,46], their perception of decisional responsibility [47], their perception of the harms and benefits of treatments [33,48-52], and their capacity to understand genetic information [53] and laboratory test results [54]. Research has also shown that lower health literacy levels among pregnant women are associated with poorer understanding of prenatal screening tests [55].…”
Section: Introductionmentioning
confidence: 99%